2009
DOI: 10.1002/rcm.4375
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of bias in static closed chamber measurement of δ13C in soil CO2 efflux

Abstract: The (13)C/(12)C ratio of soil CO(2) efflux (delta(e)) is an important parameter in studies of ecosystem C dynamics, where the accuracy of estimated C flux rates depends on the measurement uncertainty of delta(e). The static closed chamber method is frequently used in the determination of delta(e), where the soil CO(2) efflux is accumulated in the headspace of a chamber placed on top of the soil surface. However, it has recently been shown that the estimate of delta(e) obtained by using this method could be sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The values measured in the control soils in Experiment B were significantly less negative than those in the control soils in Experiment A. Following Nickerson and Risk (2009) and Ohlsson (2010), we suppose this is due to isotopic fractionation in transient-state diffusion of respired CO 2 through the soil to the purged microcosm chambers, which is expected to be greater in Experiment B for reasons discussed in Appendix A. In calculations given in Appendix A, we show that the apparent error in δ 13 C values will cause the size of the priming effect to be under-estimated, but the trends across the treatments and over time are unchanged.…”
Section: Isotope Fractionation Effectsmentioning
confidence: 66%
See 1 more Smart Citation
“…The values measured in the control soils in Experiment B were significantly less negative than those in the control soils in Experiment A. Following Nickerson and Risk (2009) and Ohlsson (2010), we suppose this is due to isotopic fractionation in transient-state diffusion of respired CO 2 through the soil to the purged microcosm chambers, which is expected to be greater in Experiment B for reasons discussed in Appendix A. In calculations given in Appendix A, we show that the apparent error in δ 13 C values will cause the size of the priming effect to be under-estimated, but the trends across the treatments and over time are unchanged.…”
Section: Isotope Fractionation Effectsmentioning
confidence: 66%
“…8 ‰ more positive than those in Experiment A. We suppose this is due to isotopic fractionation in the transient-state diffusion of respired CO 2 through the soil to the microcosm chambers, as discussed by Nickerson andRisk (2009) andOhlsson (2010). In systems using purged chambers, such as ours, this can produce a positive δ 13 C bias of up to 15 ‰ (Nickerson and Risk, 2009).…”
Section: Isotope Fractionation During δ 13 C Measurementsmentioning
confidence: 68%
“…However, in dry soils air movement through the surface of the profile may still be an issue and the skirt alters the effective footprint of the chamber. In more recent work, Ohlsson [67] mathematically evaluated a number of soilchamber sealing designs, including a chamber skirt as above, single walled chambers inserted to 0.002 and 0.025 m into the soil surface and a double walled chamber. They concluded that the latter was the most effective, but this approach has yet to be tested in the field; more work in this area is clearly desirable.…”
Section: Mixing Of Atmospheric Air In the Soil Surfacementioning
confidence: 99%
“…These feedbacks arise from non-steady-state conditions, with the build up of CO 2 in the chamber influencing the diffusion of soil CO 2 and its isotopologues, which would be an issue for all chamber systems, to a greater or lesser extent, [66] with dynamic chambers (see later) offering possibly the least disturbance. Ohlsson [67] has recently argued that, despite these findings, by careful selection of the chamber size in terms of height and area covered, the bias introduced by a closed chamber can be minimised to a point where useful isotope data can still be obtained; a modelling approach was used here, building on the work of Livingston et al [43] and Nickerson and Risk.…”
mentioning
confidence: 99%
“…Furthermore, Kayler et al (2010b) demonstrated in a field study the interrelation between perturbations of CO 2 in soil pores and aboveground measurement techniques for δ 13 C of soil respiration. Numerical approaches considering diffusion of CO 2 in soil air have been applied to simulate the impact of transient changes in environmental variables (Nickerson and Risk, 2009a;Moyes et al, 2010) or the deployment of respiration chambers (Nickerson and Risk, 2009b,c;Ohlsson, 2010) on δ 13 C efflux and, again, the disequilibrium effect. For example, CO 2 accumulating in the headspace of closed chambers and associated chamber-soil feedbacks can cause deviation of Keeling plots (Keeling, 1958) from linearity (Nickerson and Risk, 2009b;Kammer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%